2016
DOI: 10.1177/0017896916661373
|View full text |Cite
|
Sign up to set email alerts
|

SMS for sexual health: A comparison of service types and recommendations for sexual health text message service providers

Abstract: Objectives: Text message–based interventions may provide sexual health information to young people through a number of service types, from sending information on a regularly scheduled timeline, to providing an automated menu, to allowing young people to connect directly with health educators. While such service types exist, it is not clear which features young adults feel are most effective at allowing them to engage with sexual health information. Design: This study used a mixed-methods design (survey and foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(47 citation statements)
references
References 28 publications
2
45
0
Order By: Relevance
“…Forty-five per cent of the respondents to data collection messages stated that they learnt something new from the text messages, and this aligns with previous studies in which participants admit that regular texts may teach them something they had not a nticipated [88]. When compared to an Indonesian smoking cessation and sex education study which reported 95% of respondents learnt something new [80], our figure appears low.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Forty-five per cent of the respondents to data collection messages stated that they learnt something new from the text messages, and this aligns with previous studies in which participants admit that regular texts may teach them something they had not a nticipated [88]. When compared to an Indonesian smoking cessation and sex education study which reported 95% of respondents learnt something new [80], our figure appears low.…”
Section: Discussionsupporting
confidence: 80%
“…A small number of participants had privacy concerns (with regards messages being seen by partners) demonstrating the sensitive nature of some of the message content. This has been mirrored in other studies wher e participants felt more comfortable with health related texts compared to sexually themed messages [80] or were worried they may be embarrassed if someone saw the content of the messages [88]. A small number of participants felt that the messages were not appropriate to them -i.e.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations